Kelembaman Perjanjian Antariksa: Aplikasi Politis Astropolitik Dolman Terhadap Praktik Komersialisasi Antariksa (Studi Kasus Komersialisasi International Space Station) - Imanino, Ihsan (Global and Policy Journal of International Relations, 2014)
ABSTRACTThis writing proves that practices over-privatization space not conforming to conception res communis, so that the thing which renders agreement the space being inert: only having the power in a state of static. With apply the theory astropolitik Everrett C. Dolman, motivation space exploitation from developed countries such as the United States and Russia can be revealed. With an analysis environment astropolitik obtained projection strategic the exploitation of the earth orbit underlying activities over-privatization in international space station (international space station). By using vision domination of the realists, can be seen how domestic policies United States and Russia made to manipulate the exploitation of exploration project within the framework so that continuing practice over-privatization space. By the use of paradoxes res communis paradigm can be done business intepretasi reexamined listner, on the pretext so as to give only two choices.Keywords: commercialization of space, Astropolitik Dolman, Res Communis,space exploration, NASA, International Space Station, realism domination.DOI:https://doi.org/10.33005/jgp.v2i01.1977